2016
DOI: 10.1177/1077801216640382
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Sexual Attitudes Affect Women’s Judgments of Sexual Victimization Risk

Abstract: This study evaluated the effects of ethnicity, sexual attitudes, and sexual victimization history on women's judgments of sexual victimization risk in a set of dating and social scenarios. An ethnically diverse sample of undergraduate women ( n = 408) were asked to rate how risky the situations were in terms of having an unwanted sexual experience. American Indian women rated the situations as more risky than did non-Hispanic White or Hispanic women. In addition, participants with more positive attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Participants completed four paper-and-pencil measures: a demographics questionnaire, the Sociosexuality Scale (SS; Bailey, Kirk, Zhu, Dunne, & Martin, 2000), the Childhood Sexual Experiences Questionnaire (CSEQ; Finkelhor, 1979), and the Sexual Experiences Survey (SES; Koss et al, 1987). These measures were completed as part of larger questionnaire batteries in five separate, unrelated studies investigating sexual risk judgments (Crawford, Leiting, Yeater, Verney, & Lenberg, 2014; Rinehart & Yeater, 2012; Yeater, Treat, Viken, & McFall, 2010; Yeater et al, 2009). Data from these five studies informed analyses in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed four paper-and-pencil measures: a demographics questionnaire, the Sociosexuality Scale (SS; Bailey, Kirk, Zhu, Dunne, & Martin, 2000), the Childhood Sexual Experiences Questionnaire (CSEQ; Finkelhor, 1979), and the Sexual Experiences Survey (SES; Koss et al, 1987). These measures were completed as part of larger questionnaire batteries in five separate, unrelated studies investigating sexual risk judgments (Crawford, Leiting, Yeater, Verney, & Lenberg, 2014; Rinehart & Yeater, 2012; Yeater, Treat, Viken, & McFall, 2010; Yeater et al, 2009). Data from these five studies informed analyses in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Data from these five studies informed analyses in the present study. Complete information about study procedures and other measures collected in the five studies can be found in previous work (see Crawford et al, 2014; Rinehart & Yeater, 2012; Yeater et al, 2009; Yeater et al, 2010). Briefly, participants in each of the studies were undergraduate women recruited from psychology subject pools who were provided with extra credit in psychology courses for their participation.…”
Section: Methodsmentioning
confidence: 99%
“…In a related study, the California Coalition against Sexual Assault (CALCASA) (2016) found that women on college campuses age 18-24 were at greater risk for becoming victims of sexual assault, domestic violence and stalking than women in the general population. In addition, over the average span of a college career, the percentage of completed or attempted rapes among college students is between 20 and 25 percent (Crawford, et al, 2016). In addition, approximately one in five students reported being physically or sexually abused by a dating partner in 1999 (CALCASA).…”
Section: Significance and Prevalencementioning
confidence: 99%
“…College women especially, are unlikely to disclose IPV voluntarily unless asked directly about the incident (Sutherland et al, 2016). Specific numbers can also be identified among ethnic and racial groups of women in the general public when looking at the lifetime prevalence of sexual assault--with 17.7% of non-Hispanic White, 18.8% of African American, 6.8% of Asian/Pacific Islander, 34.1% of American Indian/Alaska Native, and 14.6% of Hispanic/Latina women reporting a complete rape (Crawford, Leiting, Yeater, Verney, & Lenberg, 2016). In particular, college sample populations revealed that American Indian/Alaska Native women were the predominantly high-risk group for sexual assault (Crawford, et al).…”
Section: Significance and Prevalencementioning
confidence: 99%
“…Furthermore, the SEE was developed and validated only in English, limiting its utility across language groups, and raising questions about whether existing evidence supporting its reliability and validity might be restricted to more highly acculturated (i.e., English language preference) or educated members of ethnic/racial groups. The English version of the SEE has been used in studies with Hispanic/Latino samples (e.g., Crawford et al, 2017; McLaughlin et al, 2017), but there has been virtually no psychometric evaluation of the SEE in Hispanic/Latino samples. No Spanish version of the SEE had been developed or psychometrically evaluated, and thus, it cannot be assumed that a translation would perform equivalently in both languages.…”
mentioning
confidence: 99%